Repercussões da pandemia em determinantes sociais de saúde de adolescentes - Furlan, Lucas Viero (2023)
During the Covid-19 pandemic, between 2020 and 2022, a process of precariousness of public health and social assistance policies was promoted, harming populations at risk who depend on actions and services aimed at guaranteeing fundamental rights, as listed in art. 6 of the Federal Constitution: education, health, food, work, housing, leisure, among others. With this, it is assumed that a pandemic with the proportions of Covid-19 has the potential to expand the process of vulnerability of populations that already lived without their fundamental rights guaranteed, as is the case of Brazilian adolescents in a situation of social vulnerability. Given this scenario, this dissertation aimed to investigate the repercussions of the Covid-19 pandemic on aspects that are Social Determinants of Health (SDH) of adolescents through two studies. The first study, theoretical, aimed to explore and describe the national scientific evidence on the repercussions of the Covid-19 Pandemic on Social Determinants of Health (DSS) of Brazilian adolescents. This is a Scope Review, carried out in accordance with the guidelines of the Joanna Briggs Institute. The evidence collected in the 17 selected studies indicated an increase in inequities in adolescents' access to fundamental rights during the pandemic, such as food, housing, leisure and health. However, the results of these studies refer to adolescents accessed in the hospital context, street situation, school and virtual environment, not being identified studies on populations of adolescents in other contexts, such as institutional care or socio-educational, for example. In view of the results of the scope review, the second, empirical study aimed to explore and describe the repercussions of the pandemic on the lives of adolescents who were, during the pandemic, serving a socio-educational measure in a detention unit in a city in the interior of Rio Grande do Sul. This is a qualitative and cross-sectional multiple case study carried out with four adolescents. The results showed that the pandemic increased vulnerabilities related to health, education and social protection, but hospitalization provided access to these fundamental rights. However, the repercussions of the pandemic were identified on adolescents' expectations regarding the future after the pandemic. It is concluded that the pandemic intensified vulnerabilities, especially for adolescents who were victims of inequities during their development and who were involved in the practice of infractions. In this sense, although socio-educational detention provides a certain amount of support, it seems insufficient to face the complex problem of vulnerability that demands intersectoral actions and services, encompassing public social policies for education, health and assistance. Therefore, it is understood that more investigations are needed on the problem and intersectoral actions, involving justice, health and social assistance, in order to qualify and expand the strategies for promoting, protecting and recovering the health of Brazilian adolescents.